Material disintegration affects enzymatic determination of β-glucan in barley and oats. (July 2019) - Dotsenko, Gleb; Andersson, Annica A.M.; Andersson, Roger
Abstract: Material disintegration is the primary step in β-glucan determination in cereal grains. This study investigated the effect of disintegration approach on β-glucan content, determined by an enzymatic method in mature kernels of barley and oat. Milling with a coffee grinder was found to be relevant only for pre-disintegration and homogenization of the grain (4.6% and 3.2% β-glucan content was found in barley and oats, respectively). Ball milling appeared to be the most efficient approach for reducing material particle size, but resulted in samples with underestimated β-glucan content (4.6% and 3.3% in barley and oats, respectively). Grinding with mortar and pestle in liquid nitrogen and repeated centrifugal milling were found to be the optimal disintegration methods for barley kernels (5.2% and 4.7–4.8% β-glucan content, respectively). Grinding with mortar and pestle (either in dry state or in liquid nitrogen) and single centrifugal milling were the optimal disintegration methods for oat kernels (3.6–3.9% and 3.3–3.4% β-glucan content, respectively). Highlights: Disintegration approach affects enzymatic determination of β-glucan in cereal grains. Shearing forces are more favorable than impact forces for complete β-glucan detection. Grinding with mortar and pestle in liquid nitrogen is the most efficient method. Repeated centrifugal milling is optimal for batch β-glucan analysis in barley kernels. Single centrifugal milling is optimal for batch β-glucan analysis in oat kernels.